(3GdOQI GdefJNHI ajeG UM ef GdCOhjI GdeLQHIs - (3GdbhUhfj , TeS GdOjf eMeO Hf eMeO Hf eMeO Hf HOQ GdOjf GdbhUhfj,J (B931 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPi Yde GdEfSGf eG de jYde ,haVd Gddg BOe HGdYbd GdSOjO GdCbhe , hYbO Ydi fhYg GdMjhGfi s
(3BNQgG (B:s
(3hjSJMb GdLejY SMbkG fGYekG MJi jUjQhG eKd GdgHji , Ke Ef aYI hGSJYedg YfO GdMGLI , aEfg fGaY LOkG Gddg CYde s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B56 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B11 - (3U (B260s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA GdWH (B- (3bSe GdcJGH GdChd (B- (3U (B82 ; (3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B744s
(3JHUQGJ GdCUd (B:s
(3HgG NQe s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdWHs